ANALISIS DAN EVALUASI KINERJA BUNDARAN SMP NEGERI 1 PONTIANAK - Kartika, Sulung Wahyu; ., Syafaruddin AS; ., Sumiyattinah (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
Planning the roundabout which has the shape of traffic is part of planning road that is very important. At the roundabout there is a conflict between the interests of different vehicles, the origin and purpose. The intersection of the four arms roads,  namely the General Urip Sumoharjo, HOS Cokroaminoto, Merdeka and Johar at this time regulated by roundabout. A roundabout geometric was introduced several years ago and until now have not changed, but along with the increasing population who have settled in the city of Pontianak increasingly. Based on this matter, then the purpose of writing this research was to analyze and evaluate the performance of the roundabout in existing condition. So we get an alternative plan at the intersection. In writing this research, researchers used survey methodology. Which observed the development of traffic flow on the roundabout at SMP Negeri 1 Pontianak. To conduct this research the necessary support in the form of survey tools and dvr cctv camera as recorder. Then compile the data that has been collected is processed by using The Manual Indonesian Highway Capacity (MKJI) 1997 quantitatively. Furthermore, the data that has been processed is the basis of researchers in developing an alternative plan to the roundabout in accordance with the standards for Intersection Roundabout Planning (Ministry of Settlement and Regional Infrastructure).Ultimately, this research will provide the conditions existing traffic flow patterns and geometric at the roundabout SMP Negeri 1 Pontianak 2015. Then the researchers to deduce the results of the analysis with the Manual Indonesian Highway Capacity (MKJI) 1997 and planning for the Roundabout Intersection (Ministry of Settlement and Regional Infrastructure). This is done to provide better solutions in overcoming problems of intersection in the town of Pontianak. Key words: crossroads, roundabout, traffic